2007
DOI: 10.1021/jp076894s
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Continuous-Wave-Diode Laser Cavity Ring-Down Spectroscopy of the Hydrogen Fluoride Dimer in a Pulsed Slit Jet Expansion:  Two Components of the N = 2 Triad near 1.3 μm

Abstract: The near-infrared overtone spectra of the prototypical hydrogen-bond hydrogen fluoride dimer (HF)2 contain rich information on hydrogen bond dynamics. We report a study of the N=2 triad involving excitations with two quanta of HF stretching in (HF)2 around 1.3 microm (7500-7800 cm(-1)) by means of continuous-wave-diode laser cavity ring-down spectroscopy in a pulsed supersonic slit jet expansion. The analysis of the rotationally resolved overtone spectra allows the study of vibrational mode-selective kinetics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(81 citation statements)
references
References 88 publications
0
77
1
3
Order By: Relevance
“…This field remained active [6][7][8][9][10][11], with recently renewed interest due to more stringent potential astrophysical and planetary relevance [12][13][14][15][16]. In the overtone vibrational range all previously highlighted challenges are magnified and therefore only few experimental studies were reported in the literature, such as of HF-Ar [17,18], (HF) 2 [19][20][21][22], (HCN) 2 [23], (H 2 O) 2 [24], (N 2 O) 2 [25], C 6 H 6 -Ar [26], OH-Ar [27], N 2 -HF [28], OC-HF [29] and H 2 -Ar [30]. Over recent years, the Brussels group has built an experimental set-up merging a powerful free supersonic jet and ultrasensitive high-resolution optical detection [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…This field remained active [6][7][8][9][10][11], with recently renewed interest due to more stringent potential astrophysical and planetary relevance [12][13][14][15][16]. In the overtone vibrational range all previously highlighted challenges are magnified and therefore only few experimental studies were reported in the literature, such as of HF-Ar [17,18], (HF) 2 [19][20][21][22], (HCN) 2 [23], (H 2 O) 2 [24], (N 2 O) 2 [25], C 6 H 6 -Ar [26], OH-Ar [27], N 2 -HF [28], OC-HF [29] and H 2 -Ar [30]. Over recent years, the Brussels group has built an experimental set-up merging a powerful free supersonic jet and ultrasensitive high-resolution optical detection [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, with very good data, the individual homogenous and inhomogeneous contributions can be separately evaluated (see for instance Hippler et al (2007) for an example).…”
Section: Other Sources Of Line Broadeningmentioning
confidence: 99%
“…Under optimizedreaction conditions high conversion and good chemoand enantioselectivity werea chieved at reasonably lowc atalyst/substrate andm odifier/substrate ratios.I nterestingly,t he enantioselectivity of the homogeneous system with ( R )-BINAP as ligand depends strongly on the reaction temperature, whereas the opposite holds forthe heterogeneous system. -tricyclo (tc) DNA is at hirdg eneration antisense oligonucleotide that has been extensively studied in our lab [1].Werecently becameinterestedinthe pairing properties of the -anomeric form and observed parallelo rientation in the duplexes with natural DNA and RNAc omplements [2]. Interrestingly, within its own backbone series -tc-DNA exhibits poor thermal stability whichm akes it ac andidate for strand invasion applications.W ep resent recent results on thet riplex forminga nd strand invasionp ropertieso f -tcDNA.…”
Section: Asymmetric Allylicalkylation Catalyzed By Pd/al 2 O 3 Modifimentioning
confidence: 99%
“…Thec ombination of silver and organicm aterials is important because of supramolecular or surface aspectsa nd thef ormationo fn anostructures. Therei sagrowing interest in exploitingt heir optoelectronica nd chemical properties which have potential applications in nanoelectronics [1] ,b ioanalytical processes [2] and catalysis. [3] To gain insight into moleculari nteractions of silver ions with peptidesw e used ac ombinatoriala pproach.W es ynthesized twoe ncodeds plit-and-mix peptide librariesc ontaining the amino acids D/L -Asp, D/L -Ser, D/L -His, L -Tyr( AAn), linear spacersl ikeG ly,ß -Ala,a minohexanoica cida nd turn inducing motives like Pro-Gly,P ro-Aib and trans -2-aminocyclohexane carboxylic acid ( Xn).…”
mentioning
confidence: 99%